The Effect Of Lithoid Pumice Microfiller On Increasing The Water Resistance Of Concrete - Ashot Antonyan (International Journal of Advanced Science and Technology, 2020)
The article discusses the effect of lithoid pumice microfiller on the water resistance and strength of concrete. This effect is studied in comparison with other microfillers: microsilica and bentonite.